PERFORMANCE ANALYSIS OF THE U22 WOMEN EUROPEAN BOXING CHAMPIONSHIPS - Shtanagei, Dmytro (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
In recent years, women's boxing has undergone a significant transformation, becoming not only a popular sport but also an important phenomenon within the contexts of globalization and gender equality. The refinement of athletes' training programs through analytical examination of competitive performances is deemed a critical aspect. However, only a limited number of studies have been conducted exploring the performance indicators of amateur women's boxing. The aim of the research is to determine the performance indicators of female boxers at the U22 European Championship 2023 and to conduct a comparative analysis of winners and losers. The study employs the following methods: analysis of scientific literature, video analysis of boxing bouts, and methods of mathematical statistics. This investigation analysed 12 concluding matches with 24 contenders, identifying punches and movements via video review. It was found that winners, on average, deliver 8.4% more punches and execute 13.2% more movements than their opponents throughout the bout. Analysis revealed that winners are statistically significantly more active in moving around the ring during the second and third rounds and deliver more punches in the third round.